2004
DOI: 10.1111/j.1365-2850.2004.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating first episode psychosis – the service users’ perspective: a focus group evaluation

Abstract: UK national guidance has prioritized developing specialist services for first episode psychosis. Such services are in the early stages of development and a definitive treatment model has yet to be established. The aim of this study was to explore service users' experiences of a first episode intervention designed along evidence-based 'best practice' guidelines and to establish specific elements seen as effective to help inform future service planning and provision. Twelve users of a specialist first episode se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 19 publications
1
100
1
1
Order By: Relevance
“…Previous research has noted a tendency for participants to talk specifically about their Care co-ordinators when referring to EIP services (O"Toole et al, 2004) and has suggested the influence of EIP staff views and professional backgrounds on the explanation of psychosis offered to clients (Larsen, 2007). However, the current research also suggested support offered by the EIP service had potential limits and was unable to resolve all the complex layers of the participants" ongoing journeys.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…Previous research has noted a tendency for participants to talk specifically about their Care co-ordinators when referring to EIP services (O"Toole et al, 2004) and has suggested the influence of EIP staff views and professional backgrounds on the explanation of psychosis offered to clients (Larsen, 2007). However, the current research also suggested support offered by the EIP service had potential limits and was unable to resolve all the complex layers of the participants" ongoing journeys.…”
Section: Discussioncontrasting
confidence: 37%
“…The research has provided an insight in to the aspects of an EIP service which were appreciated by service-users (O"Toole et al, 2004) and provided insights into the socio-cultural workings of an intervention (Larsen, 2007). However, limitations including the use of focus group methods, self selected samples, service-users from an experimental EIP context, and inevitable differences between EIP models delivered in different countries (Larsen, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 From a service user's perspective, being an NHS inpatient has been described as "horrible, scary, surviving the system, institutionalised, feeling strange, labelled, used in experiments, no choice". 53 Patients in this study valued one-to-one contact and personal relationships with carers, active involvement in care, choice and the feeling that their opinions mattered.…”
Section: Significance Of Psychosis For Patients In Terms Of Ill-healtmentioning
confidence: 99%
“…Empirical work examining the perspectives of firstepisode individuals and their families, 93 the risks for noncompliance, and understanding of potential risks and benefits is now being conducted, while others have begun to apply the MacCAT model to capacity assessments among prodromal and first-episode subjects. [98][99][100][101] Currently, some of the most rapid progress in psychiatric research comes from studies that examine genetic vulnerability, interactions of genetic and environmental factors on disease expression, the role of endophenotypes, and genetic and genomic determinants of treatment response. [102][103][104][105][106][107][108][109][110] However, the ethical considerations of these genetic studies have seldom been evaluated using empirical ethics methods.…”
Section: Diverse Scientific Designs and Proceduresmentioning
confidence: 99%